Management concept in skills programs at MAN 2 Boyolali Academic Year 2023/2024 - Nuruddin, Nuruddin; Yusuf, P; Supriyanto, Supriyanto (Institute of Computer Science (IOCS), 2024)
Nowadays, the need for graduates who have special skills is very much needed. To answer these challenges, MAN 2 Boyolali organizes a skills program for its students. So this research aims to find out how the skills program management is implemented at MAN 2 Boyolali. This research uses a qualitative descriptive approach that aims to describe the management of the skills program at MAN 2 Boyolali, with a research focus on automotive skills learning program. Data collection was carried out using observation, interviews and documentation techniques. Data validity techniques use source triangulation techniques and method triangulation techniques. The data analysis technique used is the Miles and Hubermen Model data analysis which consists of data reduction, data presentation, and concluding. The research results show that the learning management of the automotive skills program at MAN 2 Boyolali consists of learning planning, implementation, assessing learning processes and outcomes, and learning supervision. 1) Learning planning in the form of preparing the syllabus, making lesson plans and preparing equipment and practical materials. 2) The implementation of automotive learning is going well in a special workshop according to schedule. The learning process takes place with a scientific approach, thereby encouraging students to develop creativity and thinking in the automotive field. 3) Assessment of automotive learning processes and outcomes is based on assessment aspects, which consist of affective, psychomotor, and cognitive aspects. 4) Supervision of automotive learning is carried out by a special automotive skills coordinator appointed by the madrasa, whose task is supervising the running of the automotive skills program.